Pour une histoire comparée des cours européennes. Norbert Elias et Louis Marin : deux modèles d’interprétation - Maria Antonietta Visceglia (Bulletin du Centre de Recherche du Château de Versailles, 2013)
Both Norbert Elias and Louis Marin died in the 1990s: the German sociologist in 1990, at the age of eighty-three years and the French philosopher-semiotician in 1992 at the age of only sixty-one. While examining the work of each does not suggest contact between them, or establish relations between their respective works, neither were historians but both elaborated — within the framework of their respective disciplines — original readings of seventeenth century France, of court society and absolutism. The two approaches influenced, unequally (Elias much more than Marin) historical research and constitute, still today, a fundamental interpretation of this period that interests all those passionate about the methods and categories for interpreting the history of the court.